Oseltamivir Improved Thrombocytopenia During Veno-Arterial Extracorporeal Membrane Oxygenation in Adults With Refractory Cardiac Failure: A Single-Center Retrospective Real-World Study - Li, Yuan; Wang, Lin; Zhang, Jianning; Han, Hui; Liu, Han; Li, Chaoyang; Guo, Haipeng; Chen, Yuguo; Chen, Xiaomei (Frontiers in Cardiovascular Medicine, 2021)
Background: Severe thrombocytopenia is a common complication of extracorporeal membrane oxygenation (ECMO). Oseltamivir can be used to treat infection-associated thrombocytopenia. To evaluate the effect of oseltamivir on attenuating severe thrombocytopenia during ECMO. Methods: This was a single-center real-world study in critically ill patients supported with venous-arterial extracorporeal membrane oxygenation (VA-ECMO). Patients suspected or confirmed with influenza received oseltamivir according to the Chinese guidelines. Thrombocytopenia and survival were compared between the oseltamivir-treated and -untreated groups. The factors associated with survival were analyzed by multivariable Cox analysis. Results: A total of 82 patients were included. All patients developed thrombocytopenia after initiating VA-ECMO. Twenty-three patients received oseltamivir (O+ group), and 59 did not (O- group). During the first 8 days of VA-ECMO initiation, the platelet counts in the O+ group were higher than in the O- group (all P < 0.05). The patients in the O+ group had higher median platelet counts at the nadir (77,000/µL, 6,000-169,000/µL), compared with the O- group (49,000/µL, 2,000-168,000/µL; P = 0.04). A platelet count nadir < 50,000/µL was seen in 26% of the patients in the O+ group, compared with 53% in the O- group (P = 0.031). No significant differences in survival to discharge were seen between the O+ and O- groups (48% vs. 56%, P = 0.508). Only the Sequential Organ Failure Assessment (SOFA) scores at the time of VA-ECMO initiation were independently associated with survival (OR = 1.12, 95% confidence interval (95% CI): 1.02-1.22, P = 0.015). Conclusions: Oseltamivir could ameliorate VA-ECMO-related thrombocytopenia. These findings suggest the prophylactical potential of oseltamivir on severe thrombocytopenia associated with the initiation of VA-ECMO.